The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.5210/fm.v13i7.2123
|View full text |Cite
|
Sign up to set email alerts
|

Internet use for political mobilization: Voices of participants

Abstract: The Internet has been used extensively for U.S. presidential election campaigns since the year 2000. In 2004, Internet campaigning grew to be more interactive than in previous years. The question of whether or not the Internet is making a difference in political outcomes has become noteworthy, and research efforts have examined political campaigns via websites, characteristics of the politically active population, and roles of the media. Among various campaign forces, activities organized by the online grassro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…For example, studies have found that individuals who interact on Web 2.0 social networks are more likely to engage in sustained political participation (Bond et al 2012;Earl and Kimport 2011;Lim 2012;Sandoval-Almazan and Gil-Garcia 2014). Others have found that these interactions are associated with both partaking in public protests and a desire to maintain participation in the future (Hara 2008;Harlow 2011;Ley and Brewer 2018). While this framework has been applied to political movements, like the Women's March and the Arab Spring (Tufecki 2017), it unclear if workers use online networks in a similar fashion.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…For example, studies have found that individuals who interact on Web 2.0 social networks are more likely to engage in sustained political participation (Bond et al 2012;Earl and Kimport 2011;Lim 2012;Sandoval-Almazan and Gil-Garcia 2014). Others have found that these interactions are associated with both partaking in public protests and a desire to maintain participation in the future (Hara 2008;Harlow 2011;Ley and Brewer 2018). While this framework has been applied to political movements, like the Women's March and the Arab Spring (Tufecki 2017), it unclear if workers use online networks in a similar fashion.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In a similar vein, the array of new ICTs associated with the internet (e.g., websites, streaming videos, blogs, voice‐over‐IP, and social networking sites) has assisted numerous contemporary social movements. For example, although so‐called activists have traditionally been the primary participants in social movements, today citizens who may not consider themselves activists are participating in online mobilization (e.g., Hara, 2008). Because of the wide use of the internet, social movements are finding ways to reach the general public.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the possibility for politicians to have their own voice sent out of the party and the party's discipline (Hara 2008). In Howard's (2005) own words 'established political elites use database and Internet technologies to raise money, organize volunteers, gather intelligence on voters, and do opposition research.'…”
Section: Campaigningmentioning
confidence: 99%